2018
DOI: 10.3389/fimmu.2018.02869
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific Effects of Vaccines Illustrated Through the BCG Example: From Observations to Demonstrations

Abstract: Epidemiological studies regarding many successful vaccines suggest that vaccination may lead to a reduction in child mortality and morbidity worldwide, on a grander scale than is attributable to protection against the specific target diseases of these vaccines. These non-specific effects (NSEs) of the Bacille Calmette-Guérin (BCG) vaccine, for instance, implicate adaptive and innate immune mechanisms, with recent evidence suggesting that trained immunity might be a key instrument at play. Collectively referrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 68 publications
1
117
0
5
Order By: Relevance
“…Another Indian study [7] observed that 60% of the children with bacterial infection were without BCG scar mark. Recent evidence suggests that the effect of BCG vaccine extends beyond the target-disease immunity [32]. These non-specific effects of BCG are due to epigenetic reprogramming of innate immune cells termed "trained immunity".…”
Section: Discussionmentioning
confidence: 99%
“…Another Indian study [7] observed that 60% of the children with bacterial infection were without BCG scar mark. Recent evidence suggests that the effect of BCG vaccine extends beyond the target-disease immunity [32]. These non-specific effects of BCG are due to epigenetic reprogramming of innate immune cells termed "trained immunity".…”
Section: Discussionmentioning
confidence: 99%
“…First of all, we would like to underline the potential protective effect of Bacillus Calmette Guerin (BCG) vaccination against Covid-19 [4]. There has already been evidence showing that the BCG vaccine not only provides protection against tuberculosis, but also has a so-called heterologous immunomodulatory effect, which results in protection against various viral infections as well [5][6][7]. Its exact mechanism is not yet fully understood, but involves the activation of both heterologous lymphocytes and the trained immune system resulting in lower rates of neonatal sepsis and respiratory tract infections [5,6].…”
Section: Covid-19 and Bcgmentioning
confidence: 99%
“…Розглянута концепція стала підґрунтям для наших досліджень у напрямку конструювання ком-бінованої дифтерійної вакцини нового класу, до складу якої нами запропоновано увести комплекс поверхневих антигенів, одержаних за допомогою дезінтеграції бактеріальної маси C. diphtheriae фізичними чинниками [11,12]. Бактеріальний компонент має, по-перше, замінити собою нейротоксичний ад'ювант гідроксид алюмінію, з яким пов'язують також численні шкірні реакції у щеплених дифтерійними вакцинами [13,14], по-друге, забезпечити антиколонізаційну дію щодо збудника дифтерії та попередження бактеріоносійства, оскільки дифтерійний анатоксин не попереджає колонізацію слизових збудником дифтерії [15], по-третє, через систему уродженого імунітету він може забезпечити ряд цінних гетерологічних ефектів, підсилюючих імунний захист [16][17][18].…”
Section: Babych_em@ukrnetunclassified